Recent Advances in Metal-Oxide-Based Photoresists for EUV Lithography - Muhammad Waleed Hasan; Laura Deeb; Sergei Kumaniaev; Chenglu Wei; Kaiying Wang (Micromachines, 2024)
Extreme ultraviolet lithography (EUVL) is a leading technology in semiconductor manufacturing, enabling the creation of high-resolution patterns essential for advanced microelectronics. This review highlights recent progress in inorganic metal-oxide-based photoresists, with a focus on their applications in EUVL. The unique properties of zinc-based, tin–oxygen, and IVB group inorganic photoresists are examined, showcasing their enhanced chemical reactivity and precise patterning capabilities. Key advancements include the development of zinc oxide and tin oxide nanoparticles, which demonstrate significant improvements in photon absorption and solubility under extreme ultraviolet exposure. Additionally, the review delves into the photochemical reactions of tin–oxygen clusters and the influence of various ligands on film density and cross-linking. The findings suggest that these inorganic photoresists not only improve photolithographic performance but also hold potential for broader applications, such as pyroelectric infrared sensors and 3D printing. Future research directions are outlined, including the optimization of process parameters, the exploration of new ligand and metal combinations, and the evaluation of the environmental benefits of inorganic photoresists over traditional organic ones. These advancements are poised to further enhance the resolution and patterning capabilities required for next-generation semiconductor devices.